2022
DOI: 10.3390/nu14030518
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acid Intake during Pregnancy and Child Neuropsychological Development: A Multi-Centre Population-Based Birth Cohort Study in Spain

Abstract: Background: There are few studies that look at the intake of all types of omega-3 polyunsaturated fatty acids (n-3 PUFAs) during the different stages of pregnancy along with a long-term neuropsychological follow-up of the child. This study aims to explore the association between maternal n-3 PUFA intake during two periods of pregnancy and the child’s neuropsychological scores at different ages. Methods: Prospective data were obtained for 2644 pregnant women recruited between 2004 and 2008 in population-based b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…LC-PUFAs are involved in the function and architecture of the central nervous system throughout the various life stages. It has been shown that the LC-PUFA docosahexaenoic acid (DHA) regulates neurotransmission systems such as serotonergic, dopaminergic, norepinephrinergic, and acetylcholinergic systems [ 23 , 30 ].…”
Section: Nut Consumption and Neurodevelopment In Early Life (Gestatio...mentioning
confidence: 99%
“…LC-PUFAs are involved in the function and architecture of the central nervous system throughout the various life stages. It has been shown that the LC-PUFA docosahexaenoic acid (DHA) regulates neurotransmission systems such as serotonergic, dopaminergic, norepinephrinergic, and acetylcholinergic systems [ 23 , 30 ].…”
Section: Nut Consumption and Neurodevelopment In Early Life (Gestatio...mentioning
confidence: 99%
“…In this regard, studies show that supplementation with EPA and/or DHA may reduce pregnancy complications and benefit different maternal and newborn outcomes, with an anti-inflammatory effect on the placenta [ 18 , 19 , 20 ]. Furthermore, positive associations between maternal omega-3 PUFA intake during early pregnancy and child neuropsychological functions were found in the study by Tahaei et al [ 21 ], with prospective data from 2644 pregnant Spanish women. Compared to participants in the lowest quartile (<1.262 g/day) of omega-3 PUFA consumption during the first trimester, those children whose mothers were in the highest quartile (>1.657 g/day) had a higher general cognitive score.…”
Section: Introductionmentioning
confidence: 97%
“…The association between maternal diet and offspring neurodevelopment has been suggested by several epidemiological studies . It has been proposed that several dietary components may mediate changes in inflammatory status interfering with brain development in utero.…”
Section: Discussionmentioning
confidence: 99%